Outcome Measures for Persons With Moderate to Severe Traumatic Brain Injury: Recommendations From the American Physical Therapy Association Academy of Neurologic Physical Therapy TBI EDGE Task Force. Issue 4 (October 2016) - McCulloch, Karen L.; de Joya, Anna Lisa; Hays, Kaitlin; Donnelly, Erin; Johnson, Tammie Keller; Nirider, Coby D.; Roth, Heidi; Saliga, Sue; Ward, Irene
Abstract : Background and Purpose: The use of standardized outcome measures (OMs) is essential in assessing the effectiveness of physical therapy (PT) interventions. The purposes of this article are (1) to describe the process used by the TBI EDGE task force to assess the psychometrics and clinical utility of OMs used with individuals with moderate to severe traumatic brain injury (TBI); (2) to describe the consensus recommendations for OM use in clinical practice, research, and professional (entry-level) PT education; and (3) to make recommendations for future work. Methods: An 8-member task force used a modified Delphi process to develop recommendations on the selection of OMs for individuals with TBI. A 4-point rating scale was used to make recommendations based on practice setting and level of ambulation. Recommendations for appropriateness for research use and inclusion in entry-level education were also provided. Results: The TBI EDGE task force reviewed 88 OMs across the International Classification of Functioning, Disability, and Health (ICF) domains: 15 measured body functions/structure only, 21 measured activity only, 23 measured participation only, and 29 OMs covered more than 1 ICF domain. Discussion and Conclusions: Recommendations made by the TBI EDGE task force provide clinicians, researchers, and educators with guidance for the selection of OMs. The use of these recommendations may facilitate identification of appropriate OMs in the population with moderate to severe TBI. TBI EDGE task force recommendations can be used by clinicians, researchers, and educators when selecting OMs for their respective needs. Future efforts to update the recommendations are warranted in order to ensure that recommendations remain current and applicable. Video Abstract available for more insights from the authors (see Supplemental Digital Content 1, http://links.lww.com/JNPT/A140 ). Abstract : Supplemental Digital Content is Available in the Text.